Penguatan Kesehatan Berbasis Herbal melalui Pembuatan Minuman JALENAS (Jahe Lemon Nanas) Madu kepada Pengurus Cabang Pemudi Persis Tarogong Kaler: Strengthening Herbal-Based Health through the Production of JALENAS (Ginger, Lemon, Pineapple, and Honey) Beverage for PC Pemudi Persis Tarogong Kaler - Rantika, Nopi; Auliasari, Nurul; Handayani, Retty; Najihudin, Aji; Hindun, Siti; Sriarumtias, Framesti Frisma; Gunawan, Gilang; Nafisah, Rahayu; Sujana, Shifa Nisrina; Irmanto, Ahmad Rofi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Health is a fundamental aspect in supporting productivity, especially for teachers, who are educators of the nation's future generations. In environments prone to disease and unhealthy lifestyles, maintaining a strong immune system becomes a crucial priority. One natural and affordable way to enhance immunity is by consuming herbal drinks made from honey and medicinal plants. The objective of this community service activity was to conduct a workshop for PC Pemudi Persis Tarogong Kaler titled "Honey with All Its Nutritional and Vitamin Benefits Contains Healing" and "The Making of JALENAS Herbal Honey Drink." The methods employed included a pre-test to assess participants' understanding of honey and herbal ingredients that support sustainable health, the delivery of educational materials, a hands-on workshop, the distribution of workshop products to participants, and a post-test. Participants then completed a satisfaction questionnaire regarding the seminar, followed by the distribution of certificates and an overall evaluation. The evaluation results showed an improvement in participants' knowledge. Based on the N-Gain score calculation, the majority of participants (73.9%) experienced a moderate improvement, 17.4% experienced a high improvement, and only 2 participants (8.7%) showed no improvement (N-Gain = 0, categorized as low). The average score increased from 73.91 (pre-test) to 87.39 (post-test), indicating a clear improvement in understanding after the seminar. The average N-Gain score of 0.49 indicates a moderate level of effectiveness, meaning that the educational method used was successful but still has room for improvement, and 97% of participants expressed satisfaction with the activities conducted during the workshop.